The early inflorescence of Arabidopsis thaliana demonstrates positional effects in floral organ growth and meristem patterning - Plackett, Andrew R. G.; Powers, Stephen J.; Phillips, Andy L.; Wilson, Zoe A.; Hedden, Peter; Thomas, Stephen G. (Springer, 2018)
Most flowering plants, including the genetic model Arabidopsis thaliana, produce multiple flowers in sequence from a reproductive shoot apex to form a flower spike (inflorescence). The development of individual flowers on an Arabidopsis inflorescence has typically been considered as highly stereotypical and uniform, but this assumption is contradicted by the existence of mutants with phenotypes visible in early flowers only. This phenomenon is demonstrated by mutants partially impaired in the biosynthesis of the phytohormone gibberellin (GA), in which floral organ growth is retarded in the first flowers to be produced but has recovered spontaneously by the 10th flower. We presently lack systematic data from multiple flowers across the Arabidopsis inflorescence to explain such changes. Using mutants of the GA 20-OXIDASE (GA20ox) GA biosynthesis gene family to manipulate endogenous GA levels, we investigated the dynamics of changing floral organ growth across the early Arabidopsis inflorescence (flowers 1-10). Modelling of floral organ lengths identified a significant, GA-independent gradient of increasing stamen length relative to the pistil in the wild-type inflorescence that was separable from other, GA-dependent effects. It was also found that the first flowers exhibited unstable organ patterning in contrast to later flowers, and that this instability was prolonged by exogenous GA treatment. These findings indicate that the development of individual flowers is influenced by hitherto-unknown factors acting across the inflorescence, and also suggest novel functions for GA in floral patterning.